Appropriate use criteria for coronary angiography: a single centre experience() - Silenzi, Simona (Int J Cardiol Heart Vasc, 2020)
BACKGROUND: Increasing attention is being given to the rational use of invasive procedures. In this study, we aimed to evaluate, among patients referred for coronary angiography, the appropriateness of cardiac catheterization according to the Appropriate Use Criteria (AUC) for diagnostic catheterization and to examine the relationship between the appropriateness and the presence of obstructive coronary artery disease (CAD) and revascularization. METHODS: From November 2017 to December 2018, 1188 consecutive patients referred to undergo a diagnostic catheterization were included. They were categorized as having appropriate, uncertain or inappropriate indication, using a database (Melograno System). We restricted our analysis to 9 appropriate indications including acute coronary syndromes, suspected CAD, valvular heart disease, arrhythmias and cardiomyopathy. We restricted the analysis to the subgroup of patients with suspected or known CAD and, among them, we evaluate the rate of CAD and the need for revascularization. RESULTS: The indications were appropriate in 1017 patients (85.6%), of uncertain appropriateness in 134 (11.3%), and inappropriate in 37 (3.1%). Restricting the analysis to the CAD subgroup, the indications were appropriate in 848 patients (83.3%), of uncertain appropriateness in 133 (13.1%) and inappropriate in 37 (3.6%). The proportion of patients with critical CAD were 75.9%, 44.3% and 29.7% in the appropriate, uncertain and inappropriate categories respectively (p < 0.001). The revascularization rate was 63.1%, 32.2% and 21.6% in the appropriate, uncertain and inappropriate categories respectively (p < 0.001). CONCLUSIONS: Application of AUC is feasible in a community setting. Melograno system is useful to improve patient care.